Mechanisms of drought tolerance in Moringa: Strategies for mitigation and adaptation – Review - Vijayaragavan, V; Sumathi, T; Irene vethamoni , P; Ravichandran, V; Raju, M (Plant Science Today, 2025)
Moringa oleifera, often called the "miracle tree," is renowned for its resilience to harsh environmental conditions, particularly drought. This review explores the mechanisms by which Moringa tolerates drought stress, making it a vital crop in arid and semi-arid regions. Morphological, physiological, biochemical, and molecular adaptations attribute the tree's drought tolerance. Key mechanisms include an extensive root system that enhances water uptake, efficient water use through stomatal regulation, and the accumulation of Osmo protectants such as proline. Additionally, Moringa activates antioxidant enzymes that mitigate oxidative stress under drought conditions, safeguarding cellular integrity. Molecular responses play a significant role as well, with the upregulation of drought-responsive genes and stress-related proteins that enhance the tree’s ability to cope with water scarcity. These adaptive traits not only contribute to Moringa's survival but also improve its productivity under water-limited conditions. Beyond its environmental resilience, Moringa holds significant socioeconomic value. Its rich nutritional content, medicinal properties, and potential for income generation make it a critical crop for addressing food security and poverty, especially in developing regions. This review highlights the importance of promoting Moringa cultivation as a sustainable agricultural practice in drought-prone areas. In conclusion, understanding and leveraging Moringa's drought tolerance mechanisms can contribute to climate change mitigation and adaptation strategies. Expanding its cultivation could lead to more resilient agricultural systems, providing both environmental and socioeconomic benefits. Continued research is essential to optimize its use and ensure its widespread adoption in vulnerable regions.